Maternal prenatal thyroid function and trajectories of offspring emotional and behavioural problems: findings from the ALSPAC cohort. - Fetene, Dagnachew Muluye; Betts, Kim S.; Scott, James G.; Alati, Rosa (European Child & Adolescent Psychiatry, 2020)
Maternal thyroid hormone may have impact on fetal brain development and consequently lead to offspring mental health problems. This study examined the role of maternal prenatal thyroid function on trajectories of offspring emotional and behavioural problems. Data were taken from the Avon Longitudinal Study of Parents and Children. A total of 4839 mother–child pairs were included. Thyroid-stimulating hormone (TSH) levels, free thyroxine (FT4), and thyroid peroxidase antibodies (TPO-Ab) were assessed during the first trimester of pregnancy. Childhood emotional and behavioural problems were assessed using the Strengths and difficulties questionnaire. A group-based modelling approach was used to identify the different trajectories of offspring emotional and behavioural problems reported by parents over four waves of measurement at age 3.5 (42 months), 6.75 (81 months), 9 and 11 years. Multinomial logistic regression was then used to test for an association between hormone levels and class membership. We identified four trajectories of offspring emotional and behavioural problems; normative-decreasing (49.7%), moderate-decreasing (35.7%), moderate-static (8.4%), and high-decreasing (6.2%) trajectory. There were no significant differences in the mean values of mother's FT4, TSH, and the proportion of mothers with positive TPO-Ab between trajectories. Univariable and multivariable multinomial logistic models showed no association between maternal thyroid function (FT4, TSH, and TPO-Ab) and the trajectories of offspring emotional and behavioural problems. The results of our study show that maternal thyroid parameters in a community population are not associated with trajectories of offspring emotional and behavioural problems.